The PCR-RFLP-based Detection and Identification of the Leishmania Species Causing Human Cutaneous Leishmaniasis in the Khorasan-Razavi Province, Northeast of Iran - Anita Mohammadiha; Abdolhossein Dalimi; Mohammad Reza Mahmoodi; Mehdi Parian; Majid Pirestani; Mehdi Mohebali (Tehran University of Medical Sciences, 2017)
Background: Leishmania tropica, the causative agent of anthroponotic cutaneous leishmaniasis (ACL), and Leishmania major, which causes zoonotic cutaneous leishmaniasis (ZCL), are endemic in Iran. Methods: Cross-sectional study was designed to identify Leishmania species in cutaneous leishmaniasis patients who referred to Mashhad Health Centers from 2013 to 2014 using ITS-PCR-RFLP technique. First, physical examinations were performed in all suspected patients and CL cases were confirmed with microscopical examinations. A questionnaire was prepared and completed for each confirmed patient and DNA from each lesion smear was extracted, separately. The ribosomal internal transcribed spacer was amplified with appropriate primers and PCR products were digested by enzyme Taq1 restrict enzyme. Results: From all patients, 51 cases (54.3%) were men and 43 of them (45.7%) were women. The most frequent age group was 20-29 years old (27.2%). Hands, face and feet were the most common sites for appearance of skin lesions. All of the 94 cases (100%) tested found to be positive by ITS-PCR-RFLP. Overall, Leishmania species were identified in all of the 94 lesion smears which 33 (35%) of them were L. major and 61 (65%) of the remained isolates were identified L. tropica. Conclusion: Characterization of Leishmania isolates collected from different parts of Khorasan-Razavi Province showed that L. tropica is predominant agents of CL, especially in large and medium sized cities such as Mashhadand Shandiz. Moreover, this study revealed that ITS-PCR-RFLP based on our designed primers is a suitable method for species characterization.